736 PL11.04 HEALTH-RELATED QUALITY OF LIFE OF PATIENTS WITH ESOPHAGEAL CANCER FOLLOWING ESOPHAGECTOMY TREATED WITH NEOADJUVANT CHEMORADIOTHERAPY OR CHEMOTHERAPY: EUROPEAN MULTICENTER STUDY. (17th September 2021) - Schuring, Nannet; Markar, Sheraz; Hagens, Eliza R C; Jezerskyte, Egle; Sprangers, Mirjam A G; Johar, Asif; Gisbertz, Suzanne S; Berge Henegouwen, Mark I
Abstract: : Curative treatment for patients with esophageal cancer consists of neoadjuvant treatment and radical surgical resection. Two different strategies exist; patients can either be treated with perioperative chemotherapy (CT) or neoadjuvant chemoradiotherapy (CRT). Both strategies improve 5-year survival rates, it is however not known if these treatments affect long-term Health-Related Quality of Life (HR-QoL) differently. The aim of this study was to compare HR-QoL between patients following CT and CRT followed by esophagectomy for esophageal cancer. Methods: The LASER study database comprises data of a multicenter European study, with focus on HR-QoL among disease-free patients at least one year following an esophagectomy for esophageal or junctional cancer. Included patients completed the LASER, EORTC-QLQ-C30 and EORTC-QLQ-OG25 questionnaires. From this database we extracted patients either treated with CT or CRT for analysis. The primary endpoint was the mean difference in all long-term HR-QoL domains and LASER key symptom scores, using univariable and multivariable logistic regression analysis. The secondary endpoint was to compare the reported HR-QoL domain scores in the study population to the reference values of the general population. Results: Among the 565 included patients, 349 (61.8%) received CRT, and 216 (38.2%) were treated with CT. The mean age was 63.7 years (±SD 8.6), and mean time since surgery was 4.3 years (±SD 1.7). After multivariable analysis, patients treated with CT reported worse outcomes on 'Social Functioning' (∆means 4.56, p-value<0.05), more symptomatology on domains 'Insomnia' (∆means 5.65 p-value<0.05) and 'Diarrhea' (∆means 5.93 p-value<0.05) of the QLQ-C30 questionnaire, and more symptomatology on domains 'Reflux' (∆means 7.40, p-value<0.05), 'Odynophagia'(∆means 4.66 p-value<0.05) and 'Pain and discomfort'(∆means 4.34, p-value<0.05) of the QLQ-OG25 questionnaire. No differences were observed for the LASER key symptoms. Conclusion: Significant differences in favor of CRT were observed in several long-term HR-QoL domains for patients following esophagectomy for cancer. However, none of the observed differences in the reported long-term HR-QoL domains between patients treated with CT or with CRT, were clinically relevant (∆means≠ ≥ 10 points). Selection of neoadjuvant therapy should therefore be based on patient characteristics.